The development of a teacher observation profile for gifted and talented children in the visual arts : a thesis presented in partial fulfilment of the requirements for the degree of Master of Philosophy in Education, Massey University - Brandon, Jillian Beverly (Massey University, 2000)
This study investigated and developed a procedure for the identification of artistically gifted and talented children in New Zealand primary schools. The resulting teacher observational profile has two purposes: to provide a framework by which children become aware of their gifts and talents in the Visual Arts; and to provide educators with a structured approach for identifying students who are gifted and talented in the Visual Arts. The observational procedures gave information which provided the foundation for enriched and accelerated Visual Arts programmes. The action research approach focused on the improvement of teaching practice through observation methods utilising five phases in the development of the identification instrument. The first phase was an examination of the issues and practices related to identification of gifted and talented children. A comprehensive review of the general and Visual Art literature was undertaken to draw on the problems of definition, identification and application. The initial formation of the instrument was developed from the literature in collaboration with a pilot school in the second phase. The third phase was a review of the instrument by a professional panel. The fourth phase trialed the procedures on a cross-section of primary schools and age groups. The fifth phase analysed the data collected and refined the teacher observational profile. Thus, practising teachers were involved collaboratively throughout the research process. Each phase provided evidence upon which to base modifications to the instrument. The analyses of the three modifications generated three sets of data to determine whether the instrument was capable of identifying the characteristics in children to an exceptional level. The first analysis provided evidence of general and Visual Art learning characteristics in children's work samples to an exceptional level. The second analysis provided exceptional qualities along with combinations of interrelating patterns of Visual Art learning characteristics. The third analysis provided evidence of general learning characteristics. The results showed that characteristics are manifested in clusters and are independent in this instrument. The three analyses did not always identify the same children. This study revealed that without a structured system teachers in primary schools could easily overlook gifted and talented children in the Visual Arts. It is envisaged that the identification procedures presented in this thesis would be subject to further research, review and development.
Keywords: Gifted children; Identification; Education; Art; Creative ability in children - testing